Patrimonialisation et politisation de la cérémonie du Feu nouveau : du rituel au spectacle - Kristina Tiedje (Cahiers des Amériques Latines)
This article examines indigenous cultural politics through the performance of the New Fire Ceremony on the main plaza of the county-seat Tancanhuitz in the Mexican Huasteca. Since 2002, Nahua and Teenek elders have staged the New Fire Ceremony on the town plaza for tourists and in the presence of a national television program. This “mise en scène” raises the question whether the ceremony acquires new meanings. Here, we argue that the protagonists and the spectators work together to construct a new legacy through the creation of an indigenous patrimony in a space that has traditionally been associated with Mestizos. In this context, the local indigenous ceremony becomes a vehicle to transform a local religious and cultural event into a resource for identity politics at a national and international level.